SHOCKWAVE STUDY ON THE WINGS NACA 0012, NACA 64 - 206, AND NASA SC (2) - 0706 WITH Λ = 15O AT 0.85 MACH NUMBER - Dewi Puspitasari; Kasyful Warist Kiat (Asosiasi Peneliti Sriwijaya, 2021)
Airfoil is used as a basic form on aircraft wings. Airfoil on the wing of the aircraft is used to produce lift that will lift the fuselage into the air. Lifting force results from the difference in pressure between the upper surface and the lower surface of an aircraft wings. In high speed flights shockwave will occur at certain parts of the wing which will adversely affect the aerodynamic performance of the wing. Wing aerodynamic performance at high speeds can be improved in various ways, one of which is by giving a angle to the wing span called a swept angle. This study will use 3D CFD simulation methods using Ansys Fluent. The airfoil used are NACA 0012, NACA 64-206, and NASA SC (2) -0706 with a chord length of 1 m, AR = 5, and λ = 1 with backward swept angle Λ = 15 °. Free stream flow is air flowing with Mach Number = 0,85 at sea level and steady conditions. Based on the simulation results, shock occurs on the upper and lower surfaces for NACA 0012 with Cl = 0 due to symmetric airfoil, whereas shock occurs only on the upper surface for NACA 64-206 and NASA SC (2) - 0706 with a Cl / Cd value of 18.55 ( NACA 64-206) and 20.78 (NASA SC (2) - 0706). This simulation also provides a visual representation of Mach Number contour plots in the middle stretch (Midspan) of the wing and Cl and Cd data.